Evaluation of stress generation on the cortical bone and the palatal micro-implant complex during the implant-supported en masse retraction in lingual orthodontic technique using the FEM: Original research - Tarulatha Revanappa Shyagali; Dhaval Aghera (Tabriz University of Medical Sciences, 2019)
Background. This study aimed to evaluate and analyze the distribution of stresses on the palatal micro-implants and the cortical bone at the micro-implant site with optimal orthodontic retraction force in lingual orthodontics. Methods. ANSYS 12.1 software was used to construct the finite element model of the maxillary bone, teeth and the periodontal ligament along with the lingual bracket set-up with wire and the micro-implant. Six- and 8-mm micro-implants were constructed. The final model consisted of 99190 nodes and 324364 elements. A 200-gram of retraction force was applied from the micro-implant to the anterior retraction hook. The micro-implant was embedded between the second premolar and the first molar. Hyper-view software was used to get the results in X-Y-Z dimensions. Results. The maximum von Mises stresses detected were 52.543 MPa for 6-mm micro-implant and 54.489 MPa for 8-mm micro-implant. Maximum stress was at the neck of the micro-implant. The 8-mm implant model showed 6×10-3 mm of lingual displacement. The least displacement of 1×10-3 mm was noticed for both the implant models in the apico-occlusal direction. The maximum von Mises stresses in the cortical bone at the micro-implant site was 18.875 MPa for 6-mm micro-implant and 21.551 MPa for 8-mm micro-implant. Conclusion. Six-mm micro-implant can be the choice for the implant-supported lingual orthodontic retraction as it produced minimal stresses on the cortical bone, and the initial stress displacements produced on the micro-implant were also minimal.